The University Extension as an Ally in the Early Detection of Breast Cancer - Curcino Santos, Camila; Santos da Cruz, Andreza Priscilla; dos Santos Almeida, Weslaine; Almeida Zaneti, Maria das Graças; de Cássia Rocha Moreira, Rita (Guará Journal, 2019)
This report is the result of an experience  of  the extension activity which opened the activities of October Pink Campaign in 2017. It was an attempt to stimulate women to do self breast examination and, to promote gynecological examination and mammographic screening in order to detect breast cancer earlier. The early breast cancer detection and a high quality treatment will reduce mortality among women. The   breast clinical examination and mammographic   screening lead to early diagnosis. Educational actions give support to pathological tracking. In this perspective,  teachers  and  students of Nursing Course in Feira  de  Santana  State  University, as well as members of  Health  Women  Extension  and Resource Center joined  together  in  an  extensionist action  to  developed  strategies  to  carry  out  breast examinations  in  women  population  in  Santo  Estevão, a  small  town  in  Bahia.  The 40 women  that  integrate the  group  were  between 16 and 75 years old. Among them, 70% had never done a breast clinical examination during their whole life, 67% of them had never done mammographic screening and 15% of them presented breast palpable nodules. In this context, the women welcoming at-tendance represents a way to ensure the inclusion of these women in  early  diagnosis  programs. Besides  that,  they  will  develop  a  conscious ness about breast cancer. In addition, this initiative underlines the social contribution of a public university to this population.
Keywords: Breast neoplasms; Health education; Women's health